Women writing the West Indies, 1804-1939 : "a hot place, belonging to us" - O'Callaghan, Evelyn (Routledge research in postcolonial literatures, 2004)
This pioneering study surveys nineteenth- and twentieth-century narratives of the West Indies written by white women, English and Creole, with special regard to 'race' and gender.